Les soubresauts de l’Assemblée galloise : le caniche et le tigre - Monique Curcuru (Revue Française de Civilisation Britannique)
By the 1970s British political leaders had initiated a movement towards devolution, which was by no means an object of consensus. Despite the failure of the 1979 referendum, demands for devolution culminated in the setting up of the Welsh Assembly after the 1997 General Election. But the Welsh elections of May 1999 did not solve all the problems. Three seats short of an absolute majority, the Welsh Labour Party has had to make deals with the opposition parties. Moreover, the successive crises which engulfed the first leaders of the Welsh Executive have weighed heavily upon the management of the limited political autonomy devolved to Wales. The Welsh are now aiming to get a status similar to that of Scotland, while pinning their hopes for increased autonomy – which Downing Street is not ready to grant – on further integration within the European Union.